Relación entre el resultado del Test de Monofilamento y Michigan con el control metabólico en diabéticos del Centro de Salud Nº 1- Loja - Vargas Ramón, Mayra Mercedes (2020)
Diabetes mellitus is one of the leading causes of morbidity and mortality worldwide, accounting for approximately 4.6 million deaths annually. The importance of opportune and effective prevention from the earliest level of health is the key to achieving ever- progressively diminishing prevalence figures. A diabetic patient requires to first understand the origin of the disease and its management to contribute with its appropriate management, the health objective of a diabetic patient is its proper metabolic control; which contributes to diminishing complications in the short and long term, one of these is diabetic neuropathy which decreases the quality of life of the patient, family members, changes their surroundings and the relationship with society; the opportune prevention contributes to change the natural development of the disease, and prompt identification facilitates us to proceed with more instruments as healthcare professionals; for this reason, this cross-sectional research, with a quantitative, analytical approach involving a population of 114 patients, it is centered on associating metabolic monitoring with the results of the Monofilament and Michigan tests, whose outcomes have demonstrated that: 86 patients among 114 have an inappropriate metabolic management, and 20 of them presented diabetic neuropathy; in other words, over three-quarters of the population under consideration has inadequate monitoring of their metabolic control, encouraging the development of this disease. Keywords: Monofilament, diabetes, neuropathy, Michigan